Untere Einkommensgruppen noch gezielter entlasten; Provide even more targeted relief for lower income groups - Alexander S. Kritikos; Johanna Schulze Düding; Octavio Morales; Maximilian Priem (Wirtschaftsdienst, 2022)
– Prices for energy and food are currently rising extraordinarily sharply. Households with low net incomes in particular are being burdened by the price increases, in some cases dramatically. According to current inflation forecasts, price increases for the lowest-income ten percent would mean a burden of 5.3 percent of their net household income in 2022. Since the low-income deciles cannot compensate for the additional expenditure by reducing their savings rate or possible reserves, nor can they restrict their consumption behavior to a corresponding extent since they primarily consume goods and services for basic needs, it is essential to provide relief for these households. The measures already adopted by the German government are easing the burden on citizens, but they are not enough to compensate for the additional burden on lower-income households. Further aid packages should provide targeted and efficient relief for households at the lower half of the income distribution.
Keywords: D31; D10; D61; 330; Energiepreis; Niedrigeinkommen; Deutschland